Penanaman Tanaman Obat Keluarga (TOGA) untuk Meningkatkan Pengetahuan dan Pemahaman Masyarakat serta Mewujudkan Masyarakat Sehat - Adillah Afiyah Zalpa; Siregar, Nurintan; Pandiangan, Yuni Ramadhani; Harahap, Widia Aminarti; Pulungan, Mawadda Jaria; Harisul Bahri; Al Fikri (PAKAT: Jurnal Pengabdian Kepada Masyarakat, 2025)
Family Medicinal Plants (TOGA) are plants with positive pharmacological effects on the human body and are usually planted on a home or communal scale. These medicinal plants can then be used as traditional medicines that can be made easily. The plants chosen are usually plants that can be used to treat simple health problems such as flu and cough. In this community service activity, two activities are carried out separately, namely socialization and planting of medicinal plants with residents. Socialization is carried out to provide information to residents of Wadas Village regarding medicinal plants so that the medicinal plants can be useful after being planted. Planting is carried out to also increase awareness regarding land use, in addition to being a starting point for residents in cultivating medicinal plants. Planting is carried out on the village hall land so that residents can easily maintain, care for, and utilize the medicinal plants.